Hepatoprotection with a chloroform extract of Launaea procumbens against CCl4-induced injuries in rats - Khan Rahmat A; Khan Muhammad R; Ahmed Mushtaq; Sahreen Sumaira; Shah Naseer A; Shah Mir; Bokhari Jasia; Rashid Umbreen; Ahmad Bushra; Jan Shumaila (BMC, 2012)
Abstract Background Launaea procumbens (Asteraceae) is used as a folk medicine to treat hepatic disorders in Pakistan. The effect of a chloroform extract of Launaea procumbens (LPCE) was evaluated against carbon-tetrachloride (CCl4)-induced liver damage in rats. Methods To evaluate the hepatoprotective effects of LPCE, 36 male Sprague-Dawley rats were equally divided into six groups. Animals of group 1 (control) had free access to food and water. Group II received 3 ml/kg of CCl4 (30% in olive oil v/v) via the intraperitoneal route twice a week for 4 weeks. Group III received 1 ml of silymarin via gavage (100 mg/kg b.w.) after 48 h of CCl4 treatment whereas groups IV and V were given 1 ml of LPCE (100 and 200 mg/kg b.w., respectively) after 48 h of CCl4 treatment. Group VI received 1 ml of LPCE (200 mg/kg b.w.) twice a week for 4 weeks. The activities of the antioxidant enzymes catalase, peroxidase (POD), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), glutathione S-transferase (GST), glutathione reductase (GSR), glutathione (GSH) and lipid peroxidation (thiobarbituric acid reactive substances (TBARS)) were measured in liver homogenates. DNA damage, argyrophilic nucleolar organizer regions (AgNORs) counts and histopathology were studied in liver samples. Serum was analyzed for various biochemical parameters. Phytochemical composition in LPCE was determined through high-performance liquid chromatography (HPLC). Results LPCE inhibited lipid peroxidation, and reduced the activities of aspartate transaminase, alanine transaminase, alkaline phosphatase, and lactate dehydrogenase in serum induced by CCl4. GSH contents were increased as were the activities of antioxidant enzymes (catalase, SOD, GST, GSR, GSH-Px) when altered due to CCl4 hepatotoxicity. Similarly, absolute liver weight, relative liver weight and the number of hepatic lesions were reduced with co-administration of LPCE. Phyochemical analyses of LPCE indicated that it contained catechin, kaempferol, rutin, hyperoside and myricetin. Conclusion These results indicated that Launaea procumbens efficiently protected against the hepatotoxicity induced by CCl4 in rats, possibly through the antioxidant effects of flavonoids present in LPCE.